Divinyl Sulfone Cross-Linked Cyclodextrin-Based Polymeric Materials: Synthesis and Applications as Sorbents and Encapsulating Agents - Julia Morales-Sanfrutos; Francisco Javier Lopez-Jaramillo; Mahmoud A. A. Elremaily; Fernando Hernández-Mateo; Francisco Santoyo-Gonzalez (Molecules, 2015)
The aim of this study was to evaluate the crosslinking abilities of divinyl sulfone (DVS) for the preparation of novel water-insoluble cyclodextrin-based polymers (CDPs) capable of forming inclusion complexes with different guest molecules. Reaction of DVS with native α-cyclodextrin (α-CD), β-cyclodextrin (β-CD) and/or starch generates a variety of homo- and hetero-CDPs with different degrees of crosslinking as a function of the reactants’ stoichiometric ratio. The novel materials were characterized by powder X-ray diffraction, electron microscopy and for their sorption of phenol and 4-nitrophenol. They were further evaluated as sorbents with phenolic pollutants (bisphenol A and β-naphthol) and bioactive compounds (the hormone progesterone and curcumin). Data obtained from the inclusion experiments show that the degree of cross-linking has a minor influence on the yield of inclusion complex formation and highlight the important role of the CDs, supporting a sorption process based on the formation of inclusion complexes. In general, the inclusion processes are better described by a Freundlich isotherm although an important number of them can also be fitted to the Langmuir isotherm with R2 ≥ 0.9, suggesting a sorption onto a monolayer of homogeneous sites.